Elimination of Violence Against Children During the Covid-19 Pandemic based on the United Nations Convention on the Rights of the Child (UNCRC 1989) - Nurul Fatia Kurniasi; Juajir Sumardi; Iin Karita Sakharina (UIN Sunan Gunung Djati, 2022)
Violence against children is included in the highest cases of human rights violations during the Covid-19 pandemic. It will affect and has affected the lives of children throughout the world, especially in Indonesia. Children are a vulnerable group who need special protection during this pandemic because, during the pandemic, cases of violence against children are now shifting from the home. Indonesia has ratified the United Nations Convention On The Rights Of The Child (UNCRC 1989) through Presidential Decree Number 36 of 1990, in which the formation of national legislation, Indonesia must use the same principles based on the convention. The actualization of national law has been repeatedly launched to eliminate violence against children in Indonesia. The problem formulation of this research is how to eliminate violence against children in Indonesia during the Covid-19 pandemic based on the United Nations Convention On The Rights Of The Child (UNCRC 1989). The purpose of this study was to determine the extent of the state's responsibility in realizing the elimination of violence against children during the Covid-19 pandemic based on the 1989 UNCRC. This research is an empirical descriptive study. The study results show that the 1989 UNCRC has been implemented into Law Number 35 of 2014 as a form of state obligations and responsibilities. In this case, efforts to protect, recover, prevent, and eliminate violence against children in Indonesia, especially in Makassar, have not been appropriately fulfilled and are ineffective yet. This is evident from the lack of legal counseling, and the provision of legal assistance for child victims of violence has not been optimal. Hence, many children still do not get their right to feel safe and protected during the Covid-19 pandemic. It is the responsibility of all stakeholders to increase productivity, human resources, and implementation of the 1989 UNCRC to realize the elimination of child violence in Indonesia.